2008
DOI: 10.1016/j.jmwh.2008.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The Confidence to Practice Midwifery: Preceptor Influence on Student Self‐Efficacy

Abstract: The imperative for midwifery educators is to transmit to their students midwifery's unique body of knowledge and hallmarks of care that guide midwifery practice. Concerns have been raised about the ability to maintain the unique aspects of midwifery practice in a culture where routine use of intervention prevails. A theory-practice gap may lead to fewer student midwives exposed to the perspective and practices of midwifery during their clinical education. Preceptor role modeling is important to developing stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 34 publications
4
43
2
1
Order By: Relevance
“…The relationships could cause stress, which some participants considered to be eustress or strengthening and others considered distress and hampering their learning. This corresponds with the findings in several studies [13,14,16,19] and emphasizes the importance of good relationships between students and mentors.…”
Section: Midwives' Influence On Learningsupporting
confidence: 91%
See 1 more Smart Citation
“…The relationships could cause stress, which some participants considered to be eustress or strengthening and others considered distress and hampering their learning. This corresponds with the findings in several studies [13,14,16,19] and emphasizes the importance of good relationships between students and mentors.…”
Section: Midwives' Influence On Learningsupporting
confidence: 91%
“…Hunter reported that midwifery students rarely questioned the midwives' rules because senior midwives assessed their clinical competence. [12] Midwives are important in developing midwifery students' confidence in practice, [13] and in ensuring that they are competent. [14] Midwives are also important role models for midwifery students, both positively and negatively.…”
Section: Introductionmentioning
confidence: 99%
“…There is little empirical evidence to guide the development of programs for newly qualified midwives though a number of small studies point to the value of preceptorship, highlighting the importance of the quality of the preceptorship provided. 35 A supportive clinical environment is important to learning for undergraduates [36][37][38] and is equally important for new graduates. 39 In addition, there appears to be value in developing programs that are focused on the development of the clinician rather than organisational needs.…”
Section: Confidence In Working To the International Confederation Of mentioning
confidence: 99%
“…SE has also been found to predict clinical performance in nursing students. 18 In the field of midwifery, Jordan and Farley 19 found that SE can be enhanced in recent midwife graduates by appropriate instruction. Nevertheless, because SE is domain-specific, any assessment should focus on the specific task being assessed.…”
Section: Introductionmentioning
confidence: 99%